Antifungal Activity of Magnesium Oxide and Zirconium Oxide Nanoparticles Incorporated into Alginate Impression Material. In Vitro Study - Luma M. Al-Nema; Ahmed Asim Al-Ali (University of Mosul, College of Dentistry, 2022)
Aims: The aim of this study was to evaluate the antifungal effect of adding nanoparticles with different concentrations into irreversible hydrocolloid impression materials. Materials and Methods: This study evaluated the antifungal effect of MgO and ZrO2 nanoparticles by Minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) and using the Agar-Well diffusion method after incorporation of different concentrations of nanoparticles into irreversible hydrocolloid impression material. Results: The results of this study showed that MIC and MFC of magnesium oxide nanoparticles were 0.2wt% and 0.3wt% respectively and for zirconium oxide nanoparticles were 5wt% and 10wt% respectively. Conclusions: The incorporation of MgO and ZrO2 into irreversible hydrocolloid impression materials acts as antifungal agents.